Kinds of Food and Drinks in Morocco in the Period of Al-Murabteen and Al-Moahideen - المدرس المساعد بان علي محمد (College of Education for Women, 2019)
Cooking was of great importance in the Islamic Arabic culture and the people of Morocco have shown great interest in this aspect and also in the variety in the making of food. They used all kinds of meat of and have shown interest in preserving and distributing it .The people of Morocco used the additives in their cooking such as salt, saffron and many other kinds to add special flavor and taste and their cooking a distinctive flavor. Sweet and pastry, in addition to the drinks, represented another aspect of the Moroccan kitchen. At that time women were brought as slaves from Sudan and as a result they brought their experience in the making of sweets and pastry with them to Morocco, they used sugar, fat, wheat in addition to different kinds of nuts. In order to keep the high standard of food there was a quality control over food at that time and the owner of the market place was in charge of the quality of food, the cooking place and its cleanliness and they were also in charge of punishing the swindlers.